0216 Becoming A Doctor: How Simulated Practice Can Legitimise Medical Students' Participation In Clinical Practice. (1st November 2014) - Thomas, Libby; Reedy, Gabriel; Gill, Elaine
Abstract : Background: The interprofessional full-patient simulated learning setting gives medical students the opportunity to act as doctors in a multi-professional team for the first time. Having put themselves in the position of the doctor, they then have a new perspective of observing and understanding clinical practice—a perspective that persists when they return to the clinical environment as medical students. Legitimate peripheral participation, a theoretical construct developed by Lave and Wenger 1 to explain how members of a community of practice are slowly and purposefully drawn into a practice, can provide a useful lens through which to interpret some findings from this phenomenological study into medical student learning. Methods: Phenomenology 2, 3 is a qualitative approach to inquiry that seeks to understand a phenomenon from the perspective of those who experience it. Final-year medical students were interviewed after full-patient simulated learning experiences, and the results were analysed using phenomenological techniques. Results: Having put themselves in the position of the doctor in an interprofessional full-patient simulation, students have a new perspective of observing and understanding clinical practice when they return to their clinical placements. By participating in a clinical care situation, albeit in a peripheral way (with no live patient's care at stake), students articulate a new understanding of their clinical training. Their experience of being a clinical medical student has shifted from being solely a passive observer of clinical practice, to being a participant in clinical practice. This enhances the experience of clinical practice and the potential wisdom that they can gain from the setting. Culturally, it can be argued, they now sit in a more informed, and therefore empowering, position. Conclusions: Full-patient simulation can empower medical students to gain more from their clinical placements through their increased understanding of the roles they are observing, and with new confidence and knowledge to contribute. References: Lave J, Wenger E., Situated Learning: Legitimate Peripheral Participation 1991, New York, NY: Cambridge University Press Creswell JW. Qualitative Inquiry and Research Design; Choosing Among Five Approaches. 2007, London: Sage Publications Moustakas C. Phenomenological Research Methods1994, London: Sage Publications